Why Do Students Expect to Stay Longer in College? Evidence from Europe - Giorgio Brunello; Rudolf Winter-Ebmer (Institute for the Study of Labor (IZA), 2003)
We investigate the expected college completion time of European college students by using data from a survey of more than 3000 students in 10 countries. We explain observed excess time to graduation by paying special attention to labor market variables, such as unemployment, wage differentials and employment protection, and to the funding of tertiary education.
Keywords: I20; I22; 330; college completion; wage inequality; college; expectations; Studium; Dauer; Erwartungstheorie; Arbeitslosigkeit; Lohnstruktur; Studienfinanzierung; EU-Staaten